2022
DOI: 10.1093/mnras/stac2621
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric debris belts reveal the dynamical history of the companion exoplanet

Abstract: In recent years, a number of eccentric debris belts have been observed in extrasolar systems. The most common explanation for their shape is the presence of a nearby eccentric planetary companion. The gravitational perturbation from such a companion would induce periodic eccentricity variations on the planetesimals in the belt, with a range of precession frequencies. The overall expected shape is an eccentric belt with a finite minimum width. However, several observed eccentric debris discs have been found to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Kennedy (2020) hypothesized that the narrow width of the HD 202628 ring can be explained by a model in which the perturbing planet is able to excite the particle eccentricities before the gas disk dissipates. In addition, Rodet & Lai (2022) also showed that the damping of planetesimal eccentricity by disk gas or the slow growth of planetary eccentricity can also result in narrow debris rings. However, we are not interested in precisely modeling the disk's width, so we do not model the early portion of the disk's lifetime in which these interactions would be important.…”
Section: Disk Initial Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kennedy (2020) hypothesized that the narrow width of the HD 202628 ring can be explained by a model in which the perturbing planet is able to excite the particle eccentricities before the gas disk dissipates. In addition, Rodet & Lai (2022) also showed that the damping of planetesimal eccentricity by disk gas or the slow growth of planetary eccentricity can also result in narrow debris rings. However, we are not interested in precisely modeling the disk's width, so we do not model the early portion of the disk's lifetime in which these interactions would be important.…”
Section: Disk Initial Conditionsmentioning
confidence: 99%
“…Thus the existence of long-period planets on eccentric orbits such as the one posited around HD 202628 is preferentially attributed to a planet-planet scattering event (see the review by Raymond & Morbidelli 2022, and references therein). The narrow width of the debris disk could also be explained by past scattering events, though scattering events can both narrow and broaden disks (Rodet & Lai 2022).…”
Section: Introductionmentioning
confidence: 99%
“…If long-term perturbations drive the orbital eccentricity of the primary perturber of the disk, the combined action of both perturbers mutually and on the disk would need to be taken into account, including possible secular resonances (Yelverton & Kennedy 2018). Rodet & Lai (2022) explored the effects of interaction with a former protoplanetary disk and of repeated planet-planet scattering, both of which could drive perturber eccentricity while keeping the planetesimal belt narrow.…”
Section: Scope Of the Perturbation Scenariomentioning
confidence: 99%